TEACHER EDUCATION AND FEATURES OF THE CONTEMPORARY EDUCATIONAL CONTEXT - Irina G. Zakharova (Obrazovanie i Nauka)
The purpose of this paper is to study changes in the conditions of the educational process associated with the development of information and communication technologies (ICT).Methods. The main methods of the study were the analysis of scientific publications and regulatory documents, observations, interviews, surveys and questionnaires of students, the data processing, interpretation and analysis.Results. By analogy with the Web-technologies, the concept of educational context (dynamically changing conditions in which educational content is studied) is introduced. Context of educational process can be understood as special conditions, which determine educational purpose; the way (technology) in which the content must be submitted and will be studied; the feedback it is assumed. The features of the ICT context (conditions, arising from the use of ICT), which are characteristic of the current level of information environment are noted. It is shown that some of the negative features (the formalization of teaching materials, excessive use of the computer testing due to it’s simplicity, the easiness of obtaining information, etc.), have been manifested in the education to a greater extent than the features, which can enrich the educational process (multimedia, computer modeling, communications). The results of tests and interviews with undergraduates and high school students have showed that the vast majority of students actively using ICT couldn’t explain the principle of the computer operations, the organization of the Internet or social networks, the search algorithms, etc. However, they are not interested in these issues. Teachers promote superficial approach using ICT only for office work and testing. The importance of the teacher’s role in the ICT context creation achieving adequate quality of education is proved.Scientific novelty and practical significance. The research results can be used while developing basic educational programs of teacher education. The system changes in the context of the educational process have been identified due to the negative aspects of informatization. The conclusion has been made on the need for special approach to the determination of the ICT courses content, serial appropriate combination of traditional educational technology and ICT in the educational process. It has been noted that the information educational environment of modern classical university creates the conditions for the preparation of future teachers who will be ready to solve such problems.